1995
DOI: 10.1677/joe.0.1450027
|View full text |Cite
|
Sign up to set email alerts
|

Divergent regulation of rat adipocyte GLUT1 and GLUT4 glucose transporters by GH

Abstract: The effect of GH, in vivo, on the glucose transport systems of rat adipocytes has been investigated. Lowering of serum GH levels, by treatment of rats with an antiserum specific for rat GH (anti-rGH), significantly decreased serum levels of both IGF-I and insulin. Treatment with anti-rGH also increased glucose oxidation and the conversion of glucose to lipid by isolated adipocytes. Adipocyte glucose oxidation and lipid synthesis were measured in the presence of a limiting concentration of glucose and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…However, we found no increase in GLUT4 RNA. Previous reports have concluded that chronic GH treatment of 3T3-F442A adipocytes and rat adipocytes affects the redistribution of GLUT4, with no effect on the level of expression (17,18). A similar mechanism may explain our results.…”
Section: Sensitivity Responsivenesssupporting
confidence: 83%
See 1 more Smart Citation
“…However, we found no increase in GLUT4 RNA. Previous reports have concluded that chronic GH treatment of 3T3-F442A adipocytes and rat adipocytes affects the redistribution of GLUT4, with no effect on the level of expression (17,18). A similar mechanism may explain our results.…”
Section: Sensitivity Responsivenesssupporting
confidence: 83%
“…GH also has a lipolytic effect in most species, including man (15) and may induce insulin resistance (16). Chronic exposure to GH in vitro (adipocyte-derived cell line 3T3-F442A) and in vivo (rat adipocytes) decreases the amount of both GLUT1 and GLUT4 present in adipocyte plasma membrane (17,18). Only two studies have been published in which the effect of GH treatment on lipogenesis in isolated human adipocytes was studied.…”
Section: Introductionmentioning
confidence: 99%
“…toward GH-induced perturbations in insulin-responsive glucose transport cannot be excluded (59). Our results indicate that GHR increases in the adult as compared with the neonatal heart and that GH can increase the fatty acid uptake by cardiomyocytes expressing GHR.…”
Section: Gh Stimulates Hypertrophy Of Isolated Cardiomyocytes-mentioning
confidence: 63%
“…Of note, the IGF-I receptor is not expressed in the mature adipocyte [117], and, thus, the effect of systemic GH treatment on adipocyte function is not mediated by IGF-I. GH treatment in vivo [118, 119]or longer exposure of GH in vitro [120, 121, 122, 123, 124]induces a suppression of glucose metabolism in adipose tissues in the presence or absence of insulin. GH acts at multiple sites on insulin-signaling pathways to induce insulin resistance.…”
Section: Effect Of Gh On Adipocytesmentioning
confidence: 99%